An Analysis of Figurative Languages Used in Mark Manson’ Book Entitled “The Subtle Art of Not Giving a Fuck: A Counterintuitive Approach to Living A Good Life” - Fajriah Nurul Maulidia (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2022)
The objectives of the study are to identify the types of the figurative language found in the book and provide the contextual meaning of the found figurative language. The method used in collecting the data related to the subject of this research is documentation method, and this research was conducted by seeking any relevant data and information about the focus of the study from books and internet that are available for the analysis. The data collection was done by following these steps: reading the book, and then selecting sentences that have figurative language from the book. While the steps to analyze the data are identifying the types of figurative language on each sentence according to Leech, determining the contextual meaning of the figurative language, and eventually interpreting the data. The result shows that there are 274 figurative languages. Simile is at 18.2%. Afterwards, Litotes takes the second most found figurative language about 15.3%, and then Metaphor gets 14.2%. On the lowest point at 8.4 % are Personification and Irony. The rest types of figurative languages, Hyperbole, Metonymy, and Oxymoron, have various percentages at 10.9% for Hyperbole, 12.7% for Metonymy, and 12% for Oxymoron. It can be concluded that figurative language plays important roles in this book. Figurative language makes the novel more attractive to read, and helps the readers imagine the story, the circumstances, and the character based on what the author has illustrated. Hence, the imagination created by the reader is still in context of the story.